Risk factors for bovine respiratory disease in beef cattle - Smith, David R. (Animal health research reviews, 2020)
Bovine respiratory disease (BRD) is the leading cause of death in beef calves 3 weeks of age to weaning and is the leading cause of morbidity and mortality in beef feeding and finishing systems. Each outbreak of respiratory disease is the result of the completion of a sufficient cause, which might have also included components of viral and bacterial pathogens, a certain state of immunity, or other component causes of respiratory disease in cattle that we fail to understand. Disease is expressed when a sufficient cause is completed. Disease events we observe, such as the occurrence of BRD, usually have relationships with risk factors that are commonly the subject of epidemiologic research and the primary subject of this paper. However, it is important to understand that underlying systems produce those relationships and, ultimately, the occurrence of disease. The risk factors for BRD include a complex set of component causes that include bacterial and viral pathogens, level of host immunity, and environmental conditions that favor pathogen transmission and stress-induced susceptibility. During the post-weaning phase, these factors are superimposed on a system of marketing, transportation, and decisions made to support economic opportunity that further increase the risk for BRD.